2019
DOI: 10.33772/biowallacea.v5i2.5873
|View full text |Cite
|
Sign up to set email alerts
|

Keanekaragaman Coleoptera Dan Araneida Permukaan Tanah Pada Berbagai Kondisi Sanitasi Kebun Kakao Rakyat Di Kabupaten Kolaka Timur

Abstract: AbstrakPenelitian Keanekaragaman Coleoptera dan Araneida di ekosistem Perkebunan Kakao Rakyat Kabupaten Kolaka Timur telah dilaksanakan pada bulan Oktober 2014 – Juni  2015. Tujuannya untuk mengevaluasi kepadatan relatif dan keanekaragaman Coleoptera dan Araneida permukaan tanah. Pengambilan sampel dilakukan di empat kondisi sanitasi kebun yang berbeda, yaitu tanpa sanitasi (TS), sanitasi bersih (SB), sanitasi pohon (SP), dan sanitasi lahan/seresah (SS), dengan luas masing-masing kebun sebesar satu hektar. Pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Meanwhile, Syafiqah and Askarali (2018) found four orders and ten families of insects in the cocoa field at ladang UiTM Jasin, led by Hymenoptera, followed by Coleoptera, Orthoptera, and Hemiptera. Yuswana et al (2018) found six families of Coleoptera, the highest density was Scolytidae family (34.20%), classified as herbivores. The abundance of those species is supported by the behavior of farmers in cultivation, the pesticides applied, and the preferences of these insects.…”
Section: Abundance and Species Richness Of Insectmentioning
confidence: 95%
“…Meanwhile, Syafiqah and Askarali (2018) found four orders and ten families of insects in the cocoa field at ladang UiTM Jasin, led by Hymenoptera, followed by Coleoptera, Orthoptera, and Hemiptera. Yuswana et al (2018) found six families of Coleoptera, the highest density was Scolytidae family (34.20%), classified as herbivores. The abundance of those species is supported by the behavior of farmers in cultivation, the pesticides applied, and the preferences of these insects.…”
Section: Abundance and Species Richness Of Insectmentioning
confidence: 95%
“…(2017), mempertegas bahwa jenis makrofauna tanah yang tidak selalu ditemukan pada setiap bulannya seperti jenis laba-laba dan kalajengking, dapat disebabkan karena berkurangnya ketersediaan makanan. Penyebaran dan aktivitas ordo Coleoptera yang memiliki kulit tebal dihubungkan keterkaitannya dengan faktor lingkungan (curah hujan, temperatur, dan kelembaban) dimana akan melimpah setelah hujan (Yuswana, et. al., 2018).…”
Section: Hasil Dan Pembahasanunclassified